ADMINISTRATIVE AND LEGAL STATUS OF SUBJECTS OF THE STATE’S FINANCIAL SYSTEM MANAGEMENT:: INNOVATIVE STANDARDS AND SYSTEM MODERNIZATION IN UKRAINE - H. Strelchenko Оksana; O. Bass, Viktoriya; Horbach-Kudria, Ivanna; Myrhorod-Karpova, Valeriia (Revista Gênero e Interdisciplinaridade, 2021)
The relevance of this article is due to the fact that the development of economic relations and the emergence of new socio-economic conditions of public life began the thorough identification of the subjects of management of the Ukrainian financial system, outline of the key shortcomings of their activities and exploration of the ways of addressing the shortcomings. The purpose of the study: The purpose of the article is to conduct research on the functioning of the system of financial system management in Ukraine and the world. Research methods: Leading research methods are general and special research methods, including methods of logic, analysis, comparison, etc. The results of the study: The results of this study are a comparative legal analysis of the construction of a system of entities by the financial system of Ukraine, the study of the peculiarities of such formation and the selection of positive foreign experience for Ukraine. Practical significance of the study: The significance of the obtained results is reflected in the fact that this study can serve as a basis for outlining future changes to the current legislation of Ukraine on the functioning of the subjects of management of the financial system of Ukraine.